Minimally conscious state plus versus minus: Likelihood of emergence and long‐term functional independence - Roberto Llorens; Camilla Ippoliti; María Dolores Navarro; Carolina Colomer; Anny Maza; Sandra Goizueta; José Olaya; Belén Moliner; Joan Ferri; Enrique Noé (Annals of Clinical and Translational Neurology, 2024)
Abstract Objective Severe brain injuries can result in disorders of consciousness, such as the Minimally Conscious State (MCS), where individuals display intermittent yet discernible signs of conscious awareness. The varied levels of responsiveness and awareness observed in this state have spurred the progressive delineation of two subgroups within MCS, termed “plus” (MCS+) and “minus” (MCS‐). However, the clinical validity of these classifications remains uncertain. This study aimed to investigate and compare the likelihood of emergence from MCS, as well as the functional independence after emergence, in individuals categorized as in MCS+ and MCS‐. Methods Demographic and behavioral data of 80 participants, admitted as either in MCS+ (n = 30) or MCS‐ (n = 50) to a long‐term neurorehabilitation unit, were retrospectively analyzed. The neurobehavioral condition of each participant was evaluated weekly until discharge, demise, or emergence from MCS. The functional independence of those participants who emerged from MCS was assessed 6 months after emergence. Results While only about half of the individuals classified as in MCS‐ (n = 24) emerged from the MCS, all those admitted as in MCS+ did, and in a shorter postinjury period. Despite these differences, all individuals who emerged from the MCS demonstrated similar high disability and low functional independence 6 months after emergence, regardless of their state at admission. Interpretation Individuals classified as MCS+ exhibited a higher likelihood of emergence and a shorter time to emergence compared to those in MCS‐. However, the level of functional independence 6 months after emergence was found to be unrelated to the initial state at admission.